Entrepreneurship and the sustainable development goals - Apostolopoulos, Nicolas; Al-Dajani, Haya; Holt, Diane; Jones, Paul, active 2018; Newbery, Robert (Emerald Publishing Limited, 2018)
The sustainable development goals (SDGs) were launched in 2015, as a global agenda for addressing the multiplicity of social and environmental challenges that face communities around the world. But what role might entrepreneurship play in reaching these goals? In the first book of its kind, Entrepreneurship and the Sustainable Development Goals will encourage you to think about the critical role that entrepreneurship and entrepreneurs might play in supporting sustainable development. More than twenty authors from across Africa, Asia, North America, and Europe explore a fascinating mix of enterprises and sustainable development initiatives to illustrate the capacity of entrepreneurship as the engine for transforming our world and overcoming the diverse nature of these global challenges. Structured into three provocative sections this book explores, social change and entrepreneurship through the lens of the SDGs; Organisational practices and innovation towards the SDGs; Entrepreneurship, gender equality and empowerment towards the SDGs. Journey through the stories of tribal enterprises in India, to cacao framers in Ghana, small and medium sized businesses in Greece, social enterprises in Kenya, Zambia and the USA and many others to see the powerful force that entrepreneurship can be for promoting poverty alleviation and sustainable development.
Includes index.
Keywords: Sustainable development.; Entrepreneurship.; Business & Economics -- Entrepreneurship.; elektronické knihy; electronic books